The Ukrainian crisis and the question of sovereignty and territorial integrity - Jovanović, Nevena D. (Serbian political thought, 2023)
The current armed conflict between Russia and Ukraine is a consequence of their decade’s long complex and complicated relations, which was influenced by the United States and the countries of Western Europe. The organization of the referendum and signing of the decree on the annexation of Crimea and Sevastopol to the Russian Federation, and the conflicts in the Donbass that lasted until 2018 significantly damaged the political relations of these two countries, which were part of the Soviet Union until 1991, when they acquired their independence. The escalation of continuously bad relations led to an armed conflict, but also to the most significant political, economic and military crisis, and the consequences which were felt by the entire world. The topic of this research is the Ukrainian crisis with reference to the sovereignty and territorial integrity of Ukraine after the referendums and the joining of four regions (Donetsk, Lugansk, Zaporozhye and Kherson) to the Russian Federation. The article aims to indicate and emphasize that the key international actors who (in)directly participate in the conflict between Russia and Ukraine have different approaches when it comes to the sovereignty and territorial integrity of Ukraine, that is, when it comes to the sovereignty and territorial integrity of the Republic of Serbia, forgetting on respecting the principle of sovereign equality of states. In other words, since the outbreak of the armed conflict in Ukraine in February 2022, we have witnessed that member states of the international community, guided by their own national interests, can take different positions regarding the sovereignty and territorial integrity of a particular state, as a result of differently formulated policies.